2011
DOI: 10.1177/1082013211430294
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between tea polyphenols and rice starch during gelatinization

Abstract: The interaction between tea polyphenols (TPLs) and rice starch (RS) during gelatinization has been studied. In the RVA analysis, TPLs-fortified RS exhibited no clearly defined peak viscosity and hot paste viscosity. After excluding other factors, irregular viscosity changes were attributed to the strong interactions between RS and TPLs during pasting/gelatinization. Subsequently, the coupling constants of samples A (the gelatinized sample of the blend of 16% TPLs and RS) and B (the blend of 16% TPLs and gelati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(39 citation statements)
references
References 38 publications
4
34
1
Order By: Relevance
“…Several studies have reported downward trends in peak viscosity, trough viscosity and final viscosity under the influence of some phenols . These contradictory data in our study could be attributed to the poor solubility of quercetin and rutin in water.…”
Section: Resultscontrasting
confidence: 85%
See 2 more Smart Citations
“…Several studies have reported downward trends in peak viscosity, trough viscosity and final viscosity under the influence of some phenols . These contradictory data in our study could be attributed to the poor solubility of quercetin and rutin in water.…”
Section: Resultscontrasting
confidence: 85%
“…The swollen starch granules released amylose and amylopectin chains and enabled rutin and quercetin to interact with them via their active polyhydroxyl structures. In some studies, this phenol‐starch interaction was predominantly attributed to hydrogen bonds or hydrophobic interactions, which can disturb the behavior of the native starch molecule, restrict the mobility and flexibility of the amorphous region in TBS paste, especially the leaching and re‐ordering of amylose matrix . These factors may contribute to the observed reductions in the breakdown and setback of the paste.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the addition of the phenolic acid in rice starch-water matrix, during heating, seemed to have a significant effect on gelatinization properties, with stronger effects as the concentrations of caffeic acid in the mixture increase. Similar results have been also reported in literature (Karunaratne & Zhu, 2016;Wu, Lin, Chen, & Xiao, 2011;Zhu, 2015), showing that phenolic compounds interact with starch molecules during gelatinization, reduce its degree, and alter its thermal properties probably by interfering with the starch-water matrix. The potential interaction of phenolic extract constituents with the rice starch-water matrix during boiling may be a possible explanation for the concentration-dependent apparent diffusivity of the examined phenolic acids in rice kernels being observed in Table 3.…”
Section: Food Engineering Materials Science and Nanotechnologysupporting
confidence: 90%
“…Our previous research indicated that TPLs and RS exhibit hydrogen bonding interactions during gelatinization (Wu et al . ).…”
Section: Introductionmentioning
confidence: 97%